2003
DOI: 10.1177/014860710302700191
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary microcrystalline cellulose deposition from intravenous injection of oral medication in a patient receiving parenteral nutrition

Abstract: A 50-year-old man who had been dependent on home parenteral nutrition (HPN) for 24 years presented with shortness of breath. A computed tomography scan of the lungs revealed a diffuse micronodular parenchymal infiltrate. On bronchoscopy, a crystalloid material was identified. This organic material was determined to be consistent with codeine. The patient had been injecting codeine into his intravenous catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The results demonstrated that the unique component producing the gangrene was the microcrystalline cellulose, while the injection of pure codeine was harmless. Furthermore, pulmonary microcrystalline cellulose deposition from intravenous injection of codeine tablets has been reported in a patient receiving parenteral nutrition (10). The histological section of the transbronchial biopsy revealed embolism caused by microcrystalline cellulose.…”
Section: Discussionmentioning
confidence: 95%
“…The results demonstrated that the unique component producing the gangrene was the microcrystalline cellulose, while the injection of pure codeine was harmless. Furthermore, pulmonary microcrystalline cellulose deposition from intravenous injection of codeine tablets has been reported in a patient receiving parenteral nutrition (10). The histological section of the transbronchial biopsy revealed embolism caused by microcrystalline cellulose.…”
Section: Discussionmentioning
confidence: 95%
“…3,4,6 Microcrystalline cellulose can be stained with Congo red and Grocott's methenamine silver, aiding in the diagnosis. 4,6,7 There is no specific treatment for foreign body granulomatosis with the exception of lung transplantation. 3 Pulmonary hypertension associated with foreign body granulomatosis should be treated with vasodilators.…”
Section: Discussionmentioning
confidence: 99%
“…Although the insoluble excipients are harmless if ingested, intravenous injection results in embolization of these compounds to the pulmonary arterial circulation causing occlusion, thrombosis, and inflammation of the artery branches and microvasculature. [9][10][11][12][13][14] Pharmaceutical agents used in this manner have included acetaminophen/hydrocodone, codeine, hydromorphone, propoxyphene, methadone, tripelennamine, methylphenidate, and pentazocine. 10,[13][14][15][16] An all-inclusive list of drugs with a high likelihood for abuse and the excipients they contain is outside the scope of this brief case report.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Pharmaceutical agents used in this manner have included acetaminophen/hydrocodone, codeine, hydromorphone, propoxyphene, methadone, tripelennamine, methylphenidate, and pentazocine. 10,[13][14][15][16] An all-inclusive list of drugs with a high likelihood for abuse and the excipients they contain is outside the scope of this brief case report. However, Micromedex Healthcare Series Online, 17 an on-line drug database, is a useful resource that lists the excipients for many drugs, as reported by the manufacturers.…”
Section: Discussionmentioning
confidence: 99%